UNDERSTANDING AND PERCEPTION OF THE CHARACTER IMAGE BY PRIMARY SCHOOLCHILDREN IN THE PROCESS OF TEXT INTERPRETATION - Kateryna Hnatenko (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
Modern literature research works practically assert that literature is a way of thinking in imagery, and the interpretation of art works is almost always the interpretation of imagery, in other words perfect reality. Psychologists confirm that educational process in primary school should be formed on the account of both present and potential abilities of the children. Literature is an important means of pupils' development. Reading in grades 1 − 4 promotes the development of children's positive moral and will-power qualitie. With its help children perceive the world, learn to understand and love beautiful things. The writer's ideological content of a piece of literature can be revealed in images. The main objective of text interpretation in grades 1 − 4 is to promote pupils' perception and comprehension. Nowadays the changes in educational sphere require more attention to the issue of literary perception. In 2011, primary school changed the training course of "Reading" into "Literary reading," which aims at the development of the following reader's qualities: to be capable to independent reading,to perform different communicative and creative activities. However, the educational process observation showed the existence of problems in young learners' perception and understanding of literary art, and especially the role of character and its images. Today, the methodology pays attention to the quality of the perception, its depth and awareness. The efficiency level of children's literary work perception is set on the analysis of readers' activity results. Difficulties in the determination of the literary work perception level lie in various interpretations, complexity of the perception process, necessity to reflect different sides and emotions of imagination and thinking. Many scientific works are devoted to the analysis of literary texts understanding, to the role of visual images and imagination in literary text understanding. Numerous scientific researches suggest that the perception and understanding of literary works comes with the acquisition of certain knowledge about the author's creative work, composite structure of the work, its genre characteristics, etc. However, at primary school the peculiarities of learners' age development can become a complication. Psychologists and educational sphere workers, first of all, determine the fragmentation, lack of perception integrity of the children's literature by the child, dependence of this process on child's life experience and connection with practical activity. For young learners it is difficult to understand the motives and actions of the characters, relations with other characters, their goals and aspirations. At the lessons of literary reading, the teacher should help children to experience together with the character the event, to cultivate the ability of careful analysis of the text, to evaluate objectively the text and to express their attitude to it.